Composition of restorative glass-ionomer cements and its crucial role on the material properties - Bueno, Lígia Saraiva (2022)
During the years, many changes in restorative glass ionomer cements composition were performed aiming superior properties, as reduction on particles size and acid lyophilization. This thesis showed scientific evidence about GICs, from 3 articles with the following specific objectives: (1) to evaluate and correlate fluoride release with acid erosion; (2) radiopacity; (3) deeply understand the fluoride uptake process inside the cement matrix. For fluoride release test, specimens were placed in pH cycling solution, and fluoride amount measured by a fluoride-ion selective electrode for 15 days. For the acid erosion test, specimens were immersed in a lactic acid solution and their depth measured with a spring-loaded dial gauge. For radiopacity test, a dental x-ray machine was used, and superficial analysis processed for the 18 materials according to ISO 9917-7. For the third article, experimental fluoride-free glass specimens were stored KF solution for 24h and 19F MAS-NMR data was performed with SEM observation and EDX chemical analysis. The results found confirmed significant difference among restorative glass ionomer cements for amount and pattern of fluoride release, acid erosion and radiopacity. A positive correlation was found for fluoride release and acid erosion. Eleven from eighteen materials did not achieve the minimum value established by ISO for radiopacity. Composition and ratio P/L influenced the results showed. About the species found inside the cement matrix, AlF complexes are possibly formed when fluoride is uptaken by the cement, especially in the external surface, and a small amount is rereleased in the next 24h.